2008
DOI: 10.1021/cg800356v
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Chiral Solvents for Enantioselective Crystallization. 1. Evaluation of Thermodynamic Effects

Abstract: It can be expected that a chiral solvent possesses a certain potential to discriminate between two enantiomers by creating specific weak interactions and forming diastereomeric complexes which have different physical properties. Thus, for chiral solvents, there might be an asymmetry in the solubility phase diagrams that could be employed for resolution purposes. In this work, investigations were carried out to identify appropriate chiral solvents for the discrimination of enantiomers with the aid of nuclear ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 21 publications
2
23
0
4
Order By: Relevance
“…There, possible effects of thermodynamics and kinetics of crystallization might be exploited for enantioseparation. On the basis of these expectations, part 1 of this work 3 was directed toward the evaluation of thermodynamic effects on enantioselective crystallization with the help of chiral solvents. Unfortunately, there was no quantifiable effect on the solution thermodynamics since the two enantiomers exhibited no differences in their solubilities, and thus the solubility phase diagrams showed no asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…There, possible effects of thermodynamics and kinetics of crystallization might be exploited for enantioseparation. On the basis of these expectations, part 1 of this work 3 was directed toward the evaluation of thermodynamic effects on enantioselective crystallization with the help of chiral solvents. Unfortunately, there was no quantifiable effect on the solution thermodynamics since the two enantiomers exhibited no differences in their solubilities, and thus the solubility phase diagrams showed no asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Spezifisch ausgewählte Lçsungsmittel wurden auf ihre Fähigkeit untersucht, auch die Enantiomerentrennung racemischer Verbindungen zu ermçglichen. [135][136][137][138] Ausgewählte Ergebnisse werden in Abschnitt 3.3.2 näher vorgestellt.…”
Section: Optisch Aktive Lçsungsmittelunclassified
“…Obgleich in den chiralen Lçsungsmitteln kein quantifizierbarer Einfluss auf die Thermodynamik hinsichtlich unterschiedlicher Lçslichkeiten der Mandelsäure-Enantiomere beobachtet wurde, [135] zeigten sich in Untersuchungen zur Breite des metastabilen Bereichs (MZW = metastable zone width) in DET und (S)-Ethyllactat ausgeprägte kinetische selektive Inhibitionseffekte. [136] Beispielsweise ist in DET der metastabile Bereich bezüglich der primären Keimbildung für (R)-Mandelsäure schmaler als für (S)-und racemische Man- Abbildung 11.…”
Section: Angewandte Aufsätzeunclassified
“…A crystallization-based approach using chiral solvents was considered recently. 2 Regarding feasibility and yields, any asymmetry in the typical mirror symmetric ternary phase diagrams of a pair of enantiomers in a solvent should result in further improvements.…”
Section: Introductionmentioning
confidence: 99%
“…5 A few solubility measurements on chiral substances in chiral solvents do exist in literature, for which unfortunately no phase diagrams are available and no statement regarding the shape of solubility isotherms is provided. 6-10 Bosnich and Watts 9 and Mizumachi 10 reported that the solubilities of the pair of enantiomers of cis-[Co(en) 2 Cl 2 ]ClO 4 in (-)-2,3-butanediol and tri-R-diimine ruthenium(II) complexes, respectively, were different. This is considered as a highly favorable property.…”
Section: Introductionmentioning
confidence: 99%